PERANAN SUBSEKTOR KEHUTANAN DALAM PEMBANGUNAN EKONOMI DI KALIMANTAN BARAT - Satria Astana (Jurnal Penelitian Hasil Hutan, 1990)
Forestry  sub-sector has an  important  contribution to economic development  of  West Kalimantan. For the last few years  the average  contribution  per  year  in  the  gross  domestic   regional  product, the  manpower  absorbtion, the social income  earning,  the  regional  income  earning, and the foreign exchange  earning of  the region is estimated  around 11.20%, 66.69%, 81.91%, 47.9 7%, and  58.79%, respectively. The contribution  elasticities  of the five  economic   variables mentioned are 0.83, 1.03, 1.06, 0.94, and  0.75,  respectively. For the next nine  years, the  contribution  will  be still possible  to raise the  economic growth of  the  region.  After   that  periode, however, it will not be the anymore without a substantial progress in development  of  both  the production forest  resource and the secondary  wood  industry.